2022
DOI: 10.3389/froh.2022.876941
|View full text |Cite
|
Sign up to set email alerts
|

Dental Evaluation Prior to Cancer Therapy

Abstract: A comprehensive oral examination and dental care prior to the start of cancer therapy is the standard of care in many cancer centers. This is because good oral health will likely minimize the undesirable complications such as opportunistic infections during cancer therapy. As the considerations differ between anti-neoplastic regimens, this chapter discusses the indications and rationale when planning and executing a treatment plan for patients undergoing various cancer therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…[ 13 ] There is no doubt that head and neck cancer patients must seek and receive dental care as soon as possible after the diagnosis, avoiding any potential delay in initiating cancer therapy and, then, increasing the survival rates. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] There is no doubt that head and neck cancer patients must seek and receive dental care as soon as possible after the diagnosis, avoiding any potential delay in initiating cancer therapy and, then, increasing the survival rates. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Clinical decision making and treatment of oral foci varies, depending on the type of oral focus, cancer diagnosis, the nature of cancer treatment, and the risk of acute and long-term oral complications [11,13,30]. Previous research showed that 25.2% of oncology patients undergoing dental assessment when presenting with FN required dental treatment due to dental abscesses and/or periodontitis [44].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Gortzak et al [11] concluded that panoramic radiographs are essential for dental screening in medically compromised patients, and Choi et al [12] reported that a panoramic radiograph improved the efficacy of oral examination despite its insufficient accuracy for the diagnosis of dental caries, periodontal diseases, and other lesions. Recently, Yong et al [13] suggested that dental screening should include panoramic radiograph and bitewing radiographs in patients treated with high-dose myeloablative chemotherapy regimens and receiving radiotherapy involving the dentition. In contrast, guidelines applying to dental examination in general dental practice recommend that panoramic radiographs should not be routinely made, as intraoral radiographs are considered the optimal radiographic examination [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining good oral hygiene, regular dental evaluations, and appropriate dental interventions before and after treatment are essential. If the extraction of teeth cannot be salvaged, it is recommended that these extractions be carried out 10 to 21 days before the radiotherapy, ensuring the complete epithelization of the extraction sockets [ 77 ]. Furthermore, invasive or prophylactic dental procedures should be performed cautiously.…”
Section: Osteoradionecrosismentioning
confidence: 99%